2007
DOI: 10.1557/jmr.2007.0181
|View full text |Cite
|
Sign up to set email alerts
|

X-ray computed micro tomography as complementary method for the characterization of activated porous ceramic preforms

Abstract: X-ray computed micro tomography (CT) is an alternative technique to the classical methods such as mercury intrusion (MIP) and gas pycnometry (HP) to obtain the porosity, pore-size distribution, and density of porous materials. Besides the advantage of being a nondestructive method, it gives not only bulk properties, but also spatially resolved information. In the present work, uniaxially pressed porous alumina performs activated by titanium were analyzed with both the classical techniques and CT. The benefits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 44 publications
(83 reference statements)
0
9
0
Order By: Relevance
“…The average next nearest Ti interparticle distance in the activator containing layer is between 53 and 70 lm. [18] As soon as such melt bridges are established, the steel melt can propagate along the existing melt surfaces.…”
Section: Results Discussion and Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…The average next nearest Ti interparticle distance in the activator containing layer is between 53 and 70 lm. [18] As soon as such melt bridges are established, the steel melt can propagate along the existing melt surfaces.…”
Section: Results Discussion and Conclusionmentioning
confidence: 99%
“…[18] It was observed that the infiltration behaviour improves with increasing Ti particle number, but not with increasing the concentration using larger Ti particles. In order to simulate variable density and size of the activator particles three liltographic masks were prepared.…”
Section: Model Pore Experimentsmentioning
confidence: 94%
See 1 more Smart Citation
“…The average distance between activator particles is thus the most critical parameter. The maximum surface to surface distance between nearest neighbor particles for which under the given conditions infiltration was observed, is between 20 and 30 mm [35] The latter value is the average next nearest neighbor distance for A100T40 samples with 3 wt% Ti, which did not infiltrate at all. This threshold range is consistent with the observation that none of the A100T200 samples were infiltrated, in which the nearest neighbor distance is above the threshold value ($25 mm) even for the sample with the highest activator content (20 wt%; 42 mm).…”
Section: Infiltration Kineticmentioning
confidence: 88%
“…[35]. The set of experiments was made with a X3CrNiMo13-4 steel (Bö hler AG; Switzerland, Walisellen).…”
Section: Materials and Setup For Infiltration Experimentsmentioning
confidence: 99%